Frequency of Depression in Patients Suffering from Non-Epileptic Fits - Kiramat Ullah, Hussain Ahmad, Qasim Riaz, Sher Ayub Dawar, Asif Kamal, Ali Ahsan Mufti, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The most prevalent and severe type of mental disease, depression affects 60–70% of adults, primarily between the ages of 15 and 35. Not only are the patients affected by this terrible disorder, but also their care givers and families. It has long been known that depression often manifests as a variety of psychosomatic conditions, one of which is non-epileptic fits, which are typically more common in children and women than men. Therefore, the majority of patients who present to a psychiatric emergency room, outpatient department, or ward having non-epileptic fits have underlying depression. This was one of the few studies conducted on the prevalence of depression in patients experiencing non-epileptic fits in Pakistan, particularly in province, Khyber Pakhtunkhwa. Study Design and Study Area: In the psychiatry department of Khyber Teaching Hospital Peshawar, this descriptive cross-sectional study was conducted. Duration of Study: The duration of study was 06 months i.e. from 30th march, 2015 to 30th September, 2015. Materials and Methods: The study included 162 patients who presented to the hospital with non-epileptic fits and had ages ranging from 20 to 40 years. The study excluded non-consenting individuals, those with organic brain disorders, and those who had another psychiatric diagnosis already. On a proforma that was especially created, variables were recorded. The BDI depression scale was used to evaluate the depression screening process. Results: Of 193 patients, 162 met the requirements for study. The patients were estimated to have a mean age of 25.44 years, with a standard deviation of 14.25 years. Only 32 patients (20%) were female, while remaining 130 (80%) patient were male. Majority 88 (56%) individuals were uneducated. 46 people (32%) had education up to the primary level, 14 (8%) were matriculating, and 12 (4%) were graduates. 40 people (25%) were single, 94 people (58%) were wed, and 28 people (17%) were widows or widowers. 30 people (19%) were working and 132 (81%) were unemployed. 62 persons had been seeking care for more than 24 months, compared to 8 who had been doing so for less than 24 months, 20 persons for less than 18 months, 14 patients having duration of illness for less than 12 months and 12 patients of less than 6 months period of illness. Only when non-epileptic fits were linked to the depression (p value 0.004) was statistical significance observed. When depression was compared to the patient's gender, marital status, educational attainment, length of care, and occupation, there was no statistically significant difference. Conclusions: The majority of people who have non-epileptic fits also have depression. Age of onset of non-epileptic fits and depression are significantly correlated, whereas gender, educational level, marital status, occupation, length of illness, and patient's family history are not. Keyword: Psychological distress, depression, non-epileptic fits, KTH.